Laboratory diagnosis of herpesviruses - Marin, Jožica (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2000)
Most of herpesviruses infect children in early infancy. After the primary infection the virus establishes a latent infection and persists in different tissues for life. Clinical reactivations of virus tend to be mild except in immunocompromized persons in who reactivated virus may cause serious complications. The detection of herpesvirus as the etiological agent is recommended before administration of antiviral therapy. Basic approaches to laboratory diagnosis are direct examination of clinical material for infectious virus, viral antigens, detection of viral nucleic acid and detection of specific antibodies in patient sera.
Keywords: Cytomegalovirus; Diagnosis; diagnostika; herpes virusi; Herpesviridae; Herpesviridae infections; Herpesvirus 1, human; Herpesvirus 2, human; Herpesvirus 3, human; Herpesvirus 4, human; Herpesvirus 6, human; Herpesvirus 7, human; Immunologic tests; Isolation and purification; Microbiology; Microscopy, electron; Polymerase chain reaction